Інформаційно-психологічні атаки в умовах пандемії - Гуменюк, В. В.; Костін, Д. О. (ХНУРЕ, 2021)
The dissemination of fake information about COVID-19 to increase the panic, the need for information hygiene has been considered in this study. The problem of how people will feel after coming out of isolation is also important. The uncertainty of the situation, contradictory information from the media, feelings of insecurity and anxiety will cause a surge of mental disorders and neurotic states. There is a need for the introduction of methods and observance of information hygiene in the prevention of info epidemics, panic and mass psychosis that became apparent in the context of the corona virus pandemic.
Keywords: світова пандемія; інформаційні атаки; адикція; комп’ютерний синдром; психологічні залежності населення